Nuclear Energy, Environment and Public Safety: North-South Politics - Uddin, Dr. Md. Kamal (Strategic Planning for Energy and the Environment, 2023)
While many believe that the biggest problems today are the world’s struggling economies, the increase in terrorist cults, or growing populations, the greatest predicament concerns fossil fuel consumption, the resulting climate change and its repercussions. To change our pat- terns of fossil fuel consumption, key alternatives include fuel options such as renewable energy sources (e.g., solar or wind energy) and nuclear energy. As discussed in this article, renewable energy sources also have an environmental impact and are inadequate to totally meet the demands of an ever-expanding industrial civilization. Another alternative that many environmentalists are promoting is nuclear energy, which has been cited as the ultimate clean energy. At present, nuclear energy offers hope for an eco-friendly and economically-suitable energy option. This article argues that despite the challenges of public security, nuclear energy is a far better alternative than carbon-based fuels to promote sustainable de- velopment and protect against accelerated climate change.